The Effect of Cost, Innovation, and Logistic Capability on Competitive Advantage and Its Implications on Pharmaceutical Industry Supply Chain Performance - Xaviera, Reginata; Santosa, Wahyuningsih; Dewayana, Triwulandari Satitidjati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study evaluates the effects of cost, innovation, and logistics capability on competitive advantage and supply chain performance. Using appropriate analysis methods, this study found that cost, innovation, and logistics capability significantly affect competitive advantage and supply chain performance. In particular, efficient costs, continuous innovation, and good logistics capability are proven to contribute positively to increasing competitive advantage. In addition, competitive advantage also plays an important role in improving overall supply chain performance. The results of this study indicate that companies that can manage costs effectively, innovate, and develop their logistics capabilities can achieve competitive advantages that have a positive impact on their supply chain performance. These findings provide valuable insights for managerial practices and supply chain management strategies to improve competitiveness and operational efficiency.